FLOCponics: The integration of biofloc technology with plant production - Pinho, Sara M [UNESP] (2022)
FLOCponics is an alternative type of aquaponics that integrates biofloc technology (BFT) with soilless plant production. The aims of this paper are to present a detailed overview of the FLOCponics system's designs and performance, discuss their sustainability, highlight the current challenges, and give directions for future research. Data sources include papers containing the keywords bioflocs and hydroponics, aquaponics and/or plant production. In view of the small number of publications and the lack of standardization in experimental design and system setup, it was concluded that FLOCponics is still in its initial research stage. With respect to the animal and plant yields in FLOCponics, inconsistent results were found. Some investigations presented better or similar yield results in this system compared to traditional cultures, while others found the opposite. One of the key challenges of using FLOCponics is the effective control of solids. Refining the system's design was the main recommended improvement. Moreover, this paper highlights that the commercial application of FLOCponics will require extensive research that clarifies its technical and economic aspects, originating from experimental or pilot-scale setups with characteristics similar to commercial production. This review provides and discusses information that can be useful for the effective development of FLOCponics, guiding further research to make FLOCponics commercially feasible and thus contributing to sustainable aquaculture production.